A blood based 12-miRNA signature of Alzheimer disease patients - Leidinger, Petra; Backes, Christina; Deutscher, Stephanie; Schmitt, Katja; Mueller, Sabine C.; Frese, Karen S.; Haas, Jan; Ruprecht, Klemens; Paul, Friedemann; Stähler, Cord; Lang, Christoph JG; Meder, Benjamin; et al. (Genome biology, 2013)
Alzheimer disease (AD) is the most common form of dementia but the identification of reliable, early and non-invasive biomarkers remains a major challenge. We present a novel miRNA-based signature for detecting AD from blood samples.